1995
DOI: 10.1126/science.7624778
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Mouse OB Protein: Evidence for a Peripheral Signal Linking Adiposity and Central Neural Networks

Abstract: The recent positional cloning of the mouse ob gene and its human homology has provided the basis to investigate the potential role of the ob gene product in body weight regulation. A biologically active form of recombinant mouse OB protein was overexpressed and purified to near homogeneity from a bacterial expression system. Peripheral and central administration of microgram doses of OB protein reduced food intake and body weight of ob/ob and diet-induced obese mice but not in db/db obese mice. The behavioral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

39
1,768
7
71

Year Published

1996
1996
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 3,042 publications
(1,899 citation statements)
references
References 24 publications
39
1,768
7
71
Order By: Relevance
“…21,22 This was replicated entirely by small doses of leptin administered directly into the brain, suggesting that the main effect of leptin was to act as a signal from adipose tissue to the brain regarding the quantity of fat tissue stored. 23 Jeff Flier and colleagues at the Beth Israel Hospital in Boston were the first to elegantly show that leptin was most likely to have evolved as a signal for Inheritance and human obesity S O'Rahilly and IS Farooqi starvation rather than nutrient excess, in that the rapid fall of leptin in the plasma seen upon fasting was necessary for the normal neurohormonal adaptations seen with starvation in mammals. 24 Mutations in single genes involved in the central control of energy balance can lead to human obesity At this stage in the mid-1990s, the relevance of leptin to human physiology was uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…21,22 This was replicated entirely by small doses of leptin administered directly into the brain, suggesting that the main effect of leptin was to act as a signal from adipose tissue to the brain regarding the quantity of fat tissue stored. 23 Jeff Flier and colleagues at the Beth Israel Hospital in Boston were the first to elegantly show that leptin was most likely to have evolved as a signal for Inheritance and human obesity S O'Rahilly and IS Farooqi starvation rather than nutrient excess, in that the rapid fall of leptin in the plasma seen upon fasting was necessary for the normal neurohormonal adaptations seen with starvation in mammals. 24 Mutations in single genes involved in the central control of energy balance can lead to human obesity At this stage in the mid-1990s, the relevance of leptin to human physiology was uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 Leptin signals nutritional status and energy storage levels to feeding centers, through its action on the expression and release of orexigenic and anorexigenic neuropeptides, including, respectively, neuropeptide Y (NPY) and proopiomelanocortin (POMC). 4 In the arcuate nucleus, NPY and POMC neurons express the long form of leptin receptor (OB-Rb), which is functionally coupled to the Janus kinase-signal transducer and activator of transcription intracellular signalling cascade and produces an endogenous inhibitor (suppressor of cytokine signalling 3, SOCS-3) upon activation. 5 This action prompts appropriate regulation of food intake and energy expenditure processes and helps our body to maintain the amount of fat stores within a certain range.…”
Section: Introductionmentioning
confidence: 99%
“…5 This action prompts appropriate regulation of food intake and energy expenditure processes and helps our body to maintain the amount of fat stores within a certain range. 1,2,4,6,7 However, most obese people appear to be resistant to the action of leptin. In fact, the administration of this hormone, while proven to be effective in reducing fat and normalizing metabolic disorders in leptin-deficient mice and humans, has not proven to be effective in most cases of obesity.…”
Section: Introductionmentioning
confidence: 99%
“…The role of adipostat is based on the strong association between leptin gene expression, circulating leptin levels, and body fat content across animals of different genotypes (Frederich et al, 1995;McDougald et al, 1995). Leptin receptors are present in the hypothalamus (Chua et al, 1996), and increases in plasma leptin concentrations have been shown to inhibit feed intake, reduce Ld, and increase metabolic rate (Campfield et al, 1995;Halaas et al, 1997). The role of leptin as an adipostat is confirmed by the increases in plasma leptin levels (Table 4; P , 0.05) at the end of the restriction phase and when AA intake was reduced.…”
mentioning
confidence: 99%